Treatment for chronic depression : cognitive behavioral analysis system of psychoterapy (CBASP) - MacCullough, James P. (Guilford, 2000)
Part I. CBASP and the psychopathology of the patient A therapist's problems with a chronically depressed patient Introduction to chronically depressed patients and the CBASP program Understanding the psychopathology of chronically depressed patients Course patterns, comorbidity, and psychological characteristics Part II. CBASP method and procedures Strategies to enhance motivation for change Elicitation phase of Situational Analysis Remediation phase of Situational Analysis Using the therapist-patient relationship to modify behavior Measuring acquisition learning and generalized treatment effects Part III. History and other aspects of CBASP CBASP emergence on the national scene Training CBASP psychotherapists Comparison of CBASP to Beck's cognitive therapy and Klerman's interpersonal psychotherapy models Resolving common patient problems and crises Appendices Appendix A: Therapist prompts for administering Situational Analysis (PASA) Appendix B: Rating scales for adherence monitoring and for evaluating the quality of the interpersonal relationship Appendix C: Rating the presence of optimal CBASP therapist qualities and abilities